Diarylpentadienone derivatives (curcumin analogues): Synthesis and anti-inflammatory activity. Issue 8 (15th April 2017) - Wang, Zhi Sen; Chen, Liu Zeng; Zhou, Hai Pin; Liu, Xin Hua; Chen, Fei Hu
Graphical abstract: New diarylpentadienone derivatives were synthesized. The results revealed that compound3i showed the highest anti-inflammatory activity on decreasing IL-6. The further study showed that title compound3i inhibited expression of proteins p-p65, iNOS, COX-2 LPS-induced. Highlights: A series of unsymmetrical diarylpentadienones were synthesized. Title compound showed high anti-inflammatory activity on decreasing IL-6. Title compound could lightly reduce activation p65 in nuclei. Abstract: A series of new (2 E, 4 E )-1-(substitutedphenyl)-5-(substitutedphenyl)penta-2, 4-dien-1-one derivatives were designed and synthesized. Compounds3i, 3k were determined by X-ray. All of the compounds have been screened for their anti-inflammatory activity characterized by evaluating their inhibition against LPS-induced IL-6 and TNF-α release in cell RAW 264.7 stimulated with LPS. Compound3i showed the highest anti-inflammatory activity on decreasing IL-6 and TNF-α. The further study showed that title compound3i inhibited expression of proteins p-p65, iNOS, COX-2 LPS-induced. Immunofluorescence also revealed compound3i could lightly reduce activation p65 in nuclei. These results indicate that compound3i anti-inflammatory role may partly due to its inhibitory effect on the NF-κB signaling pathway.